20.Yüzyıl Osmanlı Periyodiklerinde Hat - Bayuk, Safiye (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2020)
Türk Hat sanatı 19. yüzyılda ve 20.yüzyılın ilk çeyreğinde en parlak dönemini yaşamış, 1928 yılında yapılan harf inklâbıyla beraber, bazı zorluklarla karşılaşılsa da bu dönemde yetişen hat sanatkârları, Türk hat sanatının itibarını korumayı ve gelecek nesillere aktarmayı başarmışlardır. Bu tez çalışmamızda 20. Yüzyıl hat sanatına genel olarak değinildikten sonra, köklü bir geleneğe sahip olan ve sıkı bir disiplinle öğrenilen hat eğitiminin bu dönemde geçirdiği merhaleler ele alınmıştır. Çalışmamızın ikinci ve üçüncü bölümünde 19. Yüzyılda Osmanlı’da başlayan basın- yayın faaliyetlerinin tarihi seyri ele alındıktan sonra, 20. Yüzyılda yayımlanan Osmanlıca periyodik yayınlarda yer alan hat kompozisyonları incelenmiştir. Bu dönemde neşredilen süreli yayınlarda pek çok hattata ait imzalı ve imzasız hatlar mevcuttur. Gerek kapak bölümünde gerek periyodiklerin içeriğinde yer alan hat kompozisyonlarına ait görseller yayımlanma sürelerine göre sınıflandırılarak katalok bölümünde sunulmuştur.

Turkish Calligraphy had its most brilliant period in the 19th century and the first quarter of the 20th century. Even though certain difficulties were got into with the alphabet reform in 1928, the calligraphy artists who grew up during this period were able to protect the reputation of Turkish calligraphy and transfer it to future generations. In this thesis, after the general mention of 20th century calligraphy, the phases of calligraphy education, which has a deep-rooted tradition and has been learned with strict discipline, has been discussed in this period. In the second and third parts of our study, after the review of the historical course of the press and publication activities started in the Ottoman Empire in the 19th century, calligraphy compositions in Ottoman periodicals published in 20th century were examined. There are signed and unsigned calligraphies belonging to many calligraphers in the periodicals published during this period. The visuals of the calligraphy compositions included in both the cover section and the periodicals are presented in the catalog section through classifying according to their publication periods. according to their publish dates.
Calligraphy in the 20th Century Ottoman Periodicals
Keywords: Osmanlıca; 20. Yüzyılda Hat Sanatı; Periyodik Yayınlar; Medresetü’l-Hattâtîn; Harf İnklâbı; Ottoman Turkish; Calligraphy in 20th Century; Periodical Publications; Medresetü’l-Hattâtîn; Alphabet Reform